Jet Ventilation Decreases Target Motion and Increases Yield of ENB Especially in Lesions With Negative Bronchus Sign. Issue 1 (January 2020) - Webb, Tracey N.; Bonta, Dacian V.; Masters, Roger; Parks, Christopher; Bechara, Rabih
Abstract : Background: Electromagnetic navigational bronchoscopy (ENB) is used to obtain peripheral lung tissue samples for evaluation and staging of central and peripheral lung lesions. Jet ventilation delivers and maintains a sustained airway pressure at high frequency, chest wall and diaphragmatic movement is drastically reduced compared with traditional ventilation. The current study looks to examine the effectiveness of tissue sampling (diagnostic yield) while using jet ventilation on target-lesion movement when compared with traditional ventilation. Methods: A total of 36 patients received total intravenous anesthesia with both jet and traditional ventilation during ENB procedure where sensor to lesion displacement was recorded. When planning the ENB procedure, the presence or absence of a viable airway to the lesion was recorded. Sensor to lesion movement was recorded and compared for significance using χ 2 and t tests, utilizing stringent P -values. Results: Overall patients with an airway to the lesion (n=23) had a higher proportion of successful diagnostic biopsies, 83% compared with those patients that lacked an airway to the lesion (n=13) 70% proportion of successful diagnostic biopsies. When using jet ventilation, the chance of nonzero displacement was 8.3% (0.14 mm), regardless of the presence of an airway. Compared with traditional ventilation, the chance of a nonzero displacement between the sensor and target-lesion was 83% (6.4 mm), independent of airway presence to the lesions. Conclusion: In patients without an airway, jet ventilation significantly decreased target displacement when compared with traditional ventilation (2 vs. 17 mm). In patients with direct airway to the lesion, jet ventilation did not significantly decrease target displacement when compared with the traditional approach. Abstract : Supplemental Digital Content is available in the text.